Sentiment Masyarakat Terhadap Virus COVID-19 Pada Instagram Menggunakan Algoritma Naïve Bayes Classifier - Hendriani, Ade; Sianturi, Susy Katarina (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Corona virus or commonly referred to as COVID-19 is a type of disease that is very contagious and its spread is very fast and terrible that has reached the entire world, its spread is taking place and Indonesia is one of the countries affected by it, this disease is not only terrorizing human visions and threatening very quickly and killing human and animal lives in a very significant time tens of millions of people have died because of it causing its own sentiment based on the opinions contained in Instagram, this research was conducted to determine the impact of the covid-19 virus outbreak on Indonesian society by conducting a classification process using the naïve Bayes classifier algorithm and the results of this study show the percentage in the level of seeing the accuracy of data testing so that it can be concluded that the use of this algorithm is very appropriate in the process of classifying a data.